Über einen Spetialfall der vierparametrischen Mannigfaltigkeit der Geraden im vierdimensionalen projektivischen Raum - Dreimanas, A. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Дрейманас. Об одном специальном случае четырехпараметрического многообразия прямых в четырехмерном проективном пространстве A. Dreimanas. Apie vienų specialų keturparametrinės tiesių daugdaros keturmatėje projektyvinėje erdvėje atvejį.